From low sense of control to problematic smartphone use severity during Covid-19 outbreak: The mediating role of fear of missing out and the moderating role of repetitive negative thinking - Brailovskaia, Julia; Stirnberg, Jan; Rozgonjuk, Dmitri; Margraf, Jürgen; Elhai, Jon D. (PLOS ONE, 2021)
Since the outbreak of Covid-19, the use of digital devices, especially smartphones, remarkably increased. Smartphone use belongs to one’s daily routine, but can negatively impact physical and mental health, performance, and relationships if used excessively. The present study aimed to investigate potential correlates of problematic smartphone use (PSU) severity and the mechanisms underlying its development. Data of 516 smartphone users from Germany (Mage = 31.91, SDage = 12.96) were assessed via online surveys in April and May 2021. PSU severity was significantly negatively associated with sense of control. In contrast, it was significantly positively linked to fear of missing out (FoMO), repetitive negative thinking (RNT), and daily time spent on smartphone use. In a moderated mediation analysis, the negative relationship between sense of control and PSU severity was significantly mediated by FoMO. RNT significantly moderated the positive association between FoMO and PSU severity. Specifically, the higher the RNT, the stronger the relationship between FoMO and PSU. The present findings disclose potential mechanisms that could contribute to PSU. Potential ways of how to reduce PSU severity are discussed.